Outcomes after Surgical Resection of Jugular Foramen Schwannomas: Systematic Review and Meta-Analysis - Hoffman, Haydn; Maloney, Brendan B.; Draytsel, Dan Y.; Babu, Harish (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objectives We sought to perform a systematic review and meta-analysis of outcomes after surgical resection of jugular foramen schwannomas (JFSs).Design A systematic review of the literature was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.Setting PubMed, Scopus, and Embase databases were searched.Participants Case series of at least five patients undergoing surgical resection of JFSs were included.Main Outcome Measures Primary outcomes included gross total resection (GTR) and near total resection (NTR) rates, as well as a composite of the two (GTR + NTR). Additional outcomes included new or worsening cranial nerve (CN) palsies and cerebrospinal fluid (CSF) leak. Random effects models were used to generate pooled outcomes.Results A total of 25 studies comprising 567 patients were included in the study. The proportions of each tumor grade were the following: grade A (33.1%), grade B (16.1%), grade C (9.2%), and grade D (41.6%). The pooled rate of GTR was 81% (95% confidence interval [CI]: 70–88; I2 = 78.9%) and the composite GTR + NTR rate was 88% (95% CI: 81–93; I2 = 66.4%). Rates of new or worsening CN palsies were the following: 12% hearing loss (95% CI: 7–20; I2 = 69.4%), 27% dysphagia (95% CI: 20–36; I2 = 66%), 20% hoarseness (95% CI: 14–28; I2 = 62.6%), and 19% facial palsy (95% CI: 13–28; I2 = 64.6%). The pooled rate of CSF leak was 9% (95% CI: 6–15; I2 = 43.9%).Conclusion The literature suggests high GTR rates of JFSs can be achieved. However, new CN deficits are not uncommon.
Keywords: schwannoma; jugular foramen; resection; microsurgery